Reformasi Struktur Pemerintahan Dengan Berlakunya Otonomi Khusus Di Aceh - Arnita Jamil (Puslatbang KHAN, 2019)
Based on the results of the study using the normative juridical research method, that with the existence of the Special Autonomy in Aceh, the structure of the Aceh government has undergone a very significant renewal. The renewal is stated directly in Act Number 11 of 2006 concerning the Government of Aceh. Some names of new institutions, which were used in the term, and were not used, are now being used again. These terms include, the Village has been returned with the old term of Gampoeng, Mukim, Ulama Consultative Assembly, Mahkamah Syar'iyah, Wilayatul Hisbah, Aceh People's Representative Council, District / City Regional Representative Council without any regional designation, Wali Nanggroe Institution, thus also with the term Qanun for other names of Regional Regulations. This is a sign that there has been a renewal of the structure of the Government of Aceh according to Special Autonomy.